How Intensions are Affected by Preparatory Conditions - St. Shabibatul Rohmah (Pioneer: Journal of Language and Literature, 2018)
The study focused on the written discourse, of the short story entitled No Witchcraft For Sale. The texts were pragmatically interpreted based on Searle’s theory of Speeh Act. This research discussed how intensions in uttering words were affected by preparatory conditions. The goals were to explain the three aspects of Speeh Act (locution, illocution and perlocution) and to describe the effects of preparatory conditions on the intensions. The data in this study were qualitative, because they were sentences taken from the short story. This is a literary research which used the descriptive analysis. Some intensions found in the utterances were declaring, thanking, asserting, claiming, commanding, congratulating, insisting, stating, telling, exclaiming, entreating, concluding, questioning, daring, asking, greeting, and blessing. These intensions were surely affected by the preparatory conditions. Contexts played important roles in conveying intentions.